The Deubiquitinating Enzyme UCHL1 Induces Resistance to Doxorubicin in HER2+ Breast Cancer by Promoting Free Fatty Acid Synthesis - Lu, Guangxian; Li, Jianhua; Ding, Leyun; Wang, Chenping; Tang, Lian; Liu, Xin; Xu, Jinhui; Zhou, Qin; Sun, Jiantong; Wang, Wenjuan; Ding, Xinyuan (Frontiers in Oncology, 2021)
Ubiquitin C-terminal hydrolase L1 (UCHL1), which is a deubiquitinating enzyme, is known to play a role in chemoresistance in cancers. However, its potential roles and mechanisms in the chemoresistance of breast cancer (BC) remain unclear. In this study, we examined its expression in patients with BC and employed Kaplan-Meier analysis and the log-rank test for survival analyses. It was found that up-regulated UCHL1 expression was positively associated with both chemoresistance and poor prognosis, especially in patients with HER2+ BC. Moreover, UCHL1 expression was elevated in HER2+ BC cells (SK-BR-3 and BT474). Similarly, doxorubicin (DOX)-resistant BC cells (MCF-7/DOX) had higher UCHL1 levels than MCF-7 cells. CCK-8 assay showed that BC cells with higher UCHL1 levels were more resistant to DOX. Furthermore, by inhibiting UCHL1 in BC cells with elevated UCHL1 expression, we demonstrated that UCHL1 promoted DOX-resistance in BC. Mechanistically, UCHL1 probably promoted DOX-resistance of BC by upregulating free fatty acid (FFA) synthesis, as exhibited by reduced FFA synthase expression and resurrected DOX-sensitivity upon UCHL1 inhibition. Overall, UCHL1 upregulation is associated with DOX-resistance and poor prognosis in patients with HER2+ BC. UCHL1 induces DOX-resistance by upregulating FFA synthesis in HER2+ BC cells. Thus, UCHL1 might be a potential clinical target for overcoming DOX resistance in patients with HER2+ BC.